Species and index diversity of macrofungi from two different locations in East Kalimantan - ARIF, MUHAMMAD FAUZI; DEMO, HILDIANA APRILIANI DHIU; YULIANI, FERDINA; HAZMI, NUBLI; ROSADI, IMAM; YULIATIN, ERVINDA; SUGIANUR, SUGIANUR; ABRIYANTO, HERY (Jurnal Natural, 2025)
East Kalimantan represents the lowland rainforest ecosystem with a vast number of macrofungi species in Indonesia. This study aimed to evaluate the diversity of macrofungi within the two different locations in East Kalimantan. The study was conducted in several phases, including planning, survey, preparation, sampling, and data analysis. Sampling was carried out systematically in 20 20 m plots. Collected samples were processed, photographed, and identified. Ecological indices, including the Shannon-Wiener diversity index, species evenness, and the Simpson dominance index, were calculated to provide a detailed analysis of the macrofungal community structure. This study found that location 1 recorded 24 species from 21 genera, while location 2 had 22 species from 20 genera. The Shannon-Wiener diversity index indicated moderate diversity at both sites, with values of 2.82 for location 1 and 2.65 for location 2. Daedaleopsis confragosa was the most frequent and dominant species in location 1, contributing 12.03% relative density, while Marasmiellus candidus dominated location 2 with 18.51% relative density. Species evenness was medium in both locations, and the dominance index was low, highlighting the ecological significance of these fungal species in their respective habitats. The results emphasize the importance of studying fungal ecology to support conservation and sustainable environmental management. The study revealed a wide variety of macrofungi that play vital roles in the tropical ecosystems of these two locations in East Kalimantan.